2016
DOI: 10.1186/s40064-015-1632-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different methods of intravenous injection on glass particle contamination from ampules

Abstract: There have been many studies on glass particle contamination from glass ampules during the injection of glass ampules, but only the contamination from direct IV bolus injection has been measured. This research aimed to study the difference in glass particle contamination from ampules with different intravenous administration methods commonly used in clinical practice. Four methods were studied: IV bolus injection directly after immediate aspiration, IV bolus injection directly after 2 min’ delayed aspiration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 14 publications
0
8
0
4
Order By: Relevance
“…18 Parenteral ilaç uygulamalarında filtreli iğne kullanımı ile hastalarda cam partikül kontaminasyonuna bağlı gelişebilecek sağlık sorunlarını yaşama riski azaltılarak hasta güvenliği arttırılabilir. 15,19 Cam ampul formu ilaçların açılması esnasında partikül kontaminasyonunun geliştiğini ortaya koyan ve bu kontaminasyonun önlenmesinde filtreli iğne kullanımını öneren çeşitli çalışmalar mevcuttur. 7,20 Amerika Sağlık Sistemi Eczacılar Derneği ilaçların güvenli bir şekilde hazırlanması ile ilgili standartlarında tek dozlu cam ampullerin içindeki ilacın enjektöre aspire edilmesi için 5 µm filtre iğnesi kullanılması gerektiği bildirilmektedir.…”
Section: Gi̇ri̇ş 1886 Yılında Fransız Eczacı Stanislausunclassified
“…18 Parenteral ilaç uygulamalarında filtreli iğne kullanımı ile hastalarda cam partikül kontaminasyonuna bağlı gelişebilecek sağlık sorunlarını yaşama riski azaltılarak hasta güvenliği arttırılabilir. 15,19 Cam ampul formu ilaçların açılması esnasında partikül kontaminasyonunun geliştiğini ortaya koyan ve bu kontaminasyonun önlenmesinde filtreli iğne kullanımını öneren çeşitli çalışmalar mevcuttur. 7,20 Amerika Sağlık Sistemi Eczacılar Derneği ilaçların güvenli bir şekilde hazırlanması ile ilgili standartlarında tek dozlu cam ampullerin içindeki ilacın enjektöre aspire edilmesi için 5 µm filtre iğnesi kullanılması gerektiği bildirilmektedir.…”
Section: Gi̇ri̇ş 1886 Yılında Fransız Eczacı Stanislausunclassified
“…Sabon et al [20] showed that various types of aspirating techniques and ampoules have no effect on glass particle contamination. Other studies demonstrated the effectiveness of filter needles and in-line filters to reduce glass particle contamination [21,22]. Preston et al [23] recovered glass particles larger than 130 µm in size in 57 % of controlled injectable solutions.…”
Section: Particles From Glass Containersmentioning
confidence: 99%
“…Az üvegampullák kinyitásakor üvegrészecskék kerülnek a folyadékba. Ha nem tartjuk be maradéktalanul a higiéniás előírásokat, az üvegrészecskékkel baktériumok is kerülnek az oldatba [9]. Azok a gyógyszerek, amelyek támogatják a baktériumok növekedését, súlyos kórházi fertőzést okozhatnak [10], míg az antibakteriális hatásúakban elpusztulnak a kontaminált csírák [8,11,12].…”
Section: Introductionunclassified